Структура освіти дорослих у Великій Британії наприкінці XX – на початку XXI століття - Орос Ільдіко; Orosz Ildikó; Oros Ildiko (СумДПУ імені А. С. Макаренка, 2019)
Резюме. Ми поставили за мету схарактеризувати структуру освіти дорослих у Великій Британії наприкінці ХХ – на початку ХХІ століття. З'ясовано тенденції розвитку системи вищої освіти дорослих у Великій Британії (кінець XX – початок XXI століття). У статті використано методи дослідження: теоретичні (аналіз філософської, педагогічної, психологічної літератури); інтерпретаційно-аналітичний метод; метод порівняльно-історичного аналізу. Аналіз структури освіти дорослих наприкінці XX – на початку XXI століття у Великій Британії дозволяє ствердити наступне: основними рисами реформ освіти дорослого населення в зазначений період є: розробка національної кваліфікаційної шкали для професійної і вищої освіти; безперервне підвищення кваліфікації дорослих; взаємодія виробництва й науки; надання керівниками підприємств переваги робітникам, які мають ступінь бакалавра з відзнакою; збільшення кількості дорослих студентів та ЗВО для їх підготовки; реалізація ідеї громадської освіти через різні типи неформальних закладів освіти; активне запровадження дистанційних технологій; реалізація нового механізму фінансування із залученням недержавних та громадських фінансових ресурсів.

Abstract. We aimed to characterize the structure of adult education in the UK in the late XX – early XXI century. The tendencies of development of system of higher education of adults in Great Britain (late XX – early XXI century) are revealed. The article uses research methods: theoretical (analysis of philosophical, pedagogical, psychological literature); interpretive-analytical method; method of comparative-historical analysis. An analysis of adult education structure at the end of the twentieth – early twenty-first century in the UK suggests the following: the main features of adult education reform during this period are: development of a national qualification scale for vocational and higher education; continuous adult education; interaction of production and science; giving by heads of enterprises benefits to workers who have a bachelor’s degree with honors; an increase in the number of adult students and HEIs for their preparation; realization of the idea of public education through different types of non-formal education institutions; active introduction of remote technologies; implementation of a new financing mechanism involving non-governmental and public financial resources. Implementation of the principles of continuity and flexibility of adult education is provided in the UK with a system of accumulation and transfer of credit units or loans (Credit Accumulation and Transfer Scheme). In addition to the system of accumulation of credit units, the UK uses a system of accreditation of credit units for prior learning (Accreditation of Prior Learning) on the basis of the submitted portfolio by an entrant, which is assessed by an associative examination commission, which accounts for credits for students aged 25 and over. This is especially effective in applying modular education that contributes to meeting the educational needs of an adult population at high economic growth rates. The basis of the new educational paradigm was distance education.

Резюме. Мы поставили цель охарактеризовать структуру образованиѐ взрослых в Великобритании в конце ХХ – начале XXI века. Выѐснены тенденции развитиѐ системы высшего образованиѐ взрослых в Великобритании (конец XX – начало XXI века). В статье использованы методы исследованиѐ: теоретические (анализ философской, педагогической, психологической литературы) интерпретационно-аналитический метод; метод сравнительно-исторического анализа. Анализ структуры образованиѐ взрослых в конце XX – начале XXI века в Великобритании позволѐет утверждать следуящее: основными чертами реформ образованиѐ взрослого населениѐ в указанный период ѐвлѐятсѐ: разработка национальной квалификационной шкалы длѐ профессионального и высшего образованиѐ; непрерывное повышение квалификации взрослых; взаимодействие производства и науки; предоставление руководителѐми предприѐтий преимущества работникам, которые имеят степень бакалавра с отличием; увеличение количества взрослых студентов и высших учебных заведений длѐ их подготовки; реализациѐ идеи гражданского образованиѐ через различные типы неформальных учебных заведений; активное внедрение дистанционных технологий; реализациѐ нового механизма финансированиѐ с привлечением негосударственных и общественных финансовых ресурсов.
The structure of adult education in the UK in the late XX – early XXI century
http://nbuv.gov.ua/UJRN/pednauk_2019_1_17
Keywords: освіта дорослих; структура освіти дорослих; Велика Британія; тенденції розвитку системи вищої освіти дорослих; доросле населення; присвоєння кваліфікації; реформування освіти дорослого населення; adult education; adult education structure; Great Britain; tendencies of the system of higher education of adults; adult population; qualification assignment; reforming adult education